GAYA KEPEMIMPINAN EFEKTIF YANG DIINGINKAN BAGI KARYAWAN - Fathimah Nur Hidayah; Niken Ayu Kusuma Wardani; Rahayu Sri Lestari; Rahmawati, Rahmawati; Muhammad Adhimawan Wijaya (Juremi: Jurnal Riset Ekonomi, 2024)
This research was conducted on students at Buana Perjuangan University, Karawang Indonesia as workers or what are called employees. Apart from being students, they are also employees who have to manage their time to take responsibility for the work that must be determined and carried out. The work they have to carry out is always assessed by the results of the work through the quantity and quality of what they have achieved to fulfill their duties and responsibilities to them. Work will definitely be influenced by the leader or leadership and various other conflicts. With this research will discuss the desired leadership style for employees. The population of this research is students from Buana Perjuangan University, Karawang Indonesia who are working at one of the companies or places where they work, so the total population taken in this research is 28 employees using a probability sampling method based on stratified random sampling